Student Support System in Higher Education Institutions - A. , Krishnamoorthy; H. , Srimathi (International Journal of Psychosocial Rehabilitation, 2020)
The main aim of higher education institutions is to provide the best ambiance for learning and wide opportunities for the students to excel in their careers. The student support services become a common phenomenon and attracting factors that motivate and enhance the academic performance of students. The nurturing of the personal, emotional, and social well-being of students in adolescence is essential as the institutions prepare the graduates with productive roles for future social life. The study examines the support services across campuses as they impact admission, enrollment, and student life.